Modern residential wiring / student textbook - Holzman, Harvey N. (Tinley Park, IL : The Goodheart-Willcox Company, Inc., 2021)
"Modern Residential Wiring provides an introduction to electrical wiring for individuals pursuing a career in electrical fields. Content aligns with the 2020 National Electrical Code. Topics covered include residential wiring installation, repair, and troubleshooting, plus motors, low-voltage circuits, and electrical math"--
Includes index.
Keywords: Electric wiring, Interior; Dwellings -- Electric equipment